Underage Drinking - Philippe De Witte, Mack C. Mitchell Jr. (dir.) (Presses universitaires de Louvain, 2012)
The complexity and importance of underage drinking prompted ERAB and ABMRF to initiate a state of the art review. It explores the extent of underage drinking across Europe and North America, as well as our current understanding of factors that increase the risk of this behaviour and potentially effective evidence-based approaches to prevent underage drinking. Unfortunately, the problem is complex and a single solution or policy to prevent underage drinking does not exist. Nevertheless, a numb...